Factors Affecting Buffaloes’ Farmers Commitment toward Accessibility of Resources in Pemalang District, Central Java, Indonesia - Krismiwati Muatip; Hermin Purwaningsih; Alief Enstein; Oentoeng Edy Djatmiko; Sri Mastuti; Nunung Noor Hidayat; Rahayu Widiyanti; Yusmi Nur Wakhidati; Lis Safitri; Danang Nur Cahyo (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This study was aimed to measure the farmers' commitment, accessibility of resources (information, capital, and assistance), and the correlation between those variables. The research method used in the current study was the survey method. The location was purposively selected in Pemalang Regency, the regency with the largest buffalo population in Central Java Province. Three subdistricts (20%) with formal and informal farmers' groups were selected, and there were Taman, Pemalang, and Belik subdistricts. One Village was selected for each subdistrict. Respondents for informal groups were taken by census method. Respondents in formal groups were taken by random sampling, and the number of respondents followed the number of informal groups. There were 136 farmers selected as respondents. (69 from each formal and informal groups). The data were analyzed using the descriptive and rank Spearman correlation methods. The results showed that the farmers' commitment of formal group and informal group members was in the moderate and low categories respectively based on the percentage score interval scaling method. Resources accessibility of formal and informal members of the farmers' group was in the low to moderate category, but the member of formal groups was slightly better. There was a strong correlation between the accessibility of resources with the commitment in the formal groups, whereas in the informal groups there was a moderate to strong correlation between the accessibility of resources with the commitment of buffalo farmers. Based on the conclusion, this study recommend that the government should assist the informal farmer group to establish formal group with the result that would increase farmers accessibility toward information, support, and capital. That condition would increase farmers commitment to continue their buffalo farm business in Pemalang Regency.